Continuous nationwide atmospheric PCDD/F monitoring network in Taiwan (2006–2016): Variation in concentrations and apportionment of emission sources. (September 2020) - Ngo, Tuan Hung; Yang, Yu-Hsuan; Chen, Yu-Cheng; Pan, Wen Chi; Chi, Kai Hsien
Abstract: Atmospheric polychlorinated-dibenzo-dioxins/dibenzo-furans (PCDD/Fs) remains an important environmental health concern. Although the total emission inventories of PCDD/Fs in Taiwan decreased from 320 to 52.1 g-I-TEQ/year during 2002–2016, the resulting concentrations of atmospheric PCDD/F and distributions in Taiwan are unknown. We, therefore, conducted a comprehensive investigation of spatial and seasonal variations and apportioned potential sources of ambient PCDD/F concentrations in Taiwan-based on 11-year observation data. A total of 1, 008 atmospheric PCDD/F samples were collected from 25 air monitoring stations (from seven areas) and 1 background station for 2006–2016. Linear regression was used to model changes in PCDD/F concentrations. Principal component analysis (PCA) and positive matrix factorization (PMF) were used to identify potential contributors. PCDD/F concentrations in the ambient air gradually decreased during the study period, with a median concentration of 28.2 fg I-TEQ/m3 over 11 years. The highest median PCDD/F concentrations were found in the highly industrialized regions of western Taiwan (38.0–43.4 fg I-TEQ/m3). Lower concentrations were found in eastern Taiwan (∼10 fg I-TEQ/m3). Background stations reported the lowest concentrations of PCDD/Fs, with a median concentration of 1.47 fg I-TEQ/m3. Overall, the concentrations of atmospheric PCDD/Fs in Taiwan were higher in winter (13.4–86.7 fg I-TEQ/m3) than in summer (9.65–27.2 fg I-TEQ/m3). The PCA results indicated that PCDD/F profiles varied by both region (industrialized, urbanized, and background areas) and season. The PMF model for the overall data revealed that the major sources of PCDD/Fs were industrial activities (71.2%). However, in less industrialized areas, traffic activities, long-range transport, and open burning were dominant. Highlights: Atmospheric PCDD/Fs widely ranged from 0.97 to 255 fg I-TEQ/m 3 . Annual median of ambient PCDD/Fs dropped from 43.9 to 18.2 fg I-TEQ/m 3 in 11 years. Highest level of PCDD/Fs were in western Taiwan spatially and in winter seasonally. PMF showed major sources to be industry (71.2%), LRT (28.6%), and traffic (2.2%).